Influência do beiral no conforto térmico dos blocos de salas de aula do Campus Caraúbas-UFERSA - Galiza, Josué Johab de (Universidade Federal Rural do Semi-Árido, 2018)
This work analyzes the aquatic behavior in the thermal area in the Federal Rural University of Semi-Arid in the City of Caraúbas - RN, and arises-that which are in which thermal thermal discomfort. Performing the due model in the room block is due to the ion structure in some rooms, which is a solar current in rooms that fits directly to an outside wall of the window. The use of a digital thermometer can be collected as an internal and external measurement of both rooms for thermal analysis and a quantity of heat during the day. both rooms. What happened to the changes during the days, the result was once without waiting room, the energy increased with the longer duration of the with the eaves. Therefore, it is necessary to use the calibration system in the buildings to connect directly to the solar wall, consequently reducing the amount of energy.
Monografia
Keywords: Conforto térmico; Beiral; Incidência solar; Condução térmica; Transferência de calor; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA